WO3/Bi2WO6 photoanode enhancement for photoelectrocatalytic water oxidation; scan rate effect optimization in the cyclic voltammetry deposition method - Uttayanil, Titsucha; Ponchio, Chatchai (Journal of Applied Research on Science and Technology (JARST), 2023)
The photoelectrocatalytic approach is a very efficient technology for eliminating microorganisms and organic contaminants. The development of photoanode is widely recognized as a crucial approach to enhancing the efficiency of photoelectrocatalytic cells. The key goal of this methodology is to enhance the efficacy of photoelectrocatalytic oxidation by optimizing composited photoanode fabrication. This research development focuses mainly on fabricating composite WO3/Bi2WO6 semiconductor thin films with high water oxidation efficiency and favorable photoelectrocatalytic E. coli degradation applications. Cyclic voltammetry was utilized to create WO3/Bi2WO6 thin coatings on conducting glass while optimizing the photoelectrocatalytic activity via the scan rate parameter. The characteristics of the developed electrode, including charge transfer resistance, optical properties, morphology, crystal structure, chemical composition, and oxidation numbers, were investigated to improve photoelectrocatalytic activity. It was observed that the scanning rate significantly influenced the characteristics of the WO3/Bi2WO6 electrode and the photoelectrocatalytic activity on water oxidation. It was discovered that the WO3/Bi2WO6 electrode prepared with a scan rate of 25 mV/s exhibited the greatest photoelectrocatalytic water oxidation as well as distinguishing characteristics from other conditions. The decision to utilize decreased scanning rates has been determined to optimize the reaction kinetics and improve the film-forming properties of WO3/Bi2WO6. Significantly, the developed electrode can also be used to eliminate 87.5% of E.coli in 15 minutes via a photoelectrocatalytic catalytic mechanism. The photoanode composed of WO3/Bi2WO6 has promising capabilities in removing microorganisms and organic pollutants, making it a viable candidate for future advancements in wastewater management applications.